Faster for less: the new "shorter" regimen for multidrug-resistant tuberculosis. Issue 5 (1st September 2016) - Sotgiu, Giovanni; Tiberi, Simon; D'Ambrosio, Lia; Centis, Rosella; Alffenaar, Jan Willem; Caminero, Jose A.; Abdo Arbex, Marcos; Alarcon Guizado, Valentina; Aleksa, Alena; Dore, Simone; Gaga, Mina; Gualano, Gina; et al.
Multidrug resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) are growing clinical and public health concerns, with an estimated worldwide incidence and mortality of 480 000 and 190 000 cases, respectively (2014) [1]. The World Health Organization (WHO) End TB Strategy reiterates the MDR-/XDR-TB threat and the solutions to control the epidemic [2]. Unfortunately, large proportions of patients with resistant TB do not have access to adequate diagnostics and treatment yet, while treatment success rates remain suboptimal (as demonstrated in the largest retrospective cohort of MDR-TB patients, i.e., TB caused by Mycobacterium tuberculosis isolates resistant to at least isoniazid and rifampicin) and decrease further with resistance patterns beyond XDR-TB [3]. Evaluation of drug resistances is needed to identify candidates for the shorter regimen in MDR-TB hot spots http://ow.ly/wZV33022VXt